Answer:
600 Grams = 1.323 Pounds
Step-by-step explanation:
1 gram equals 0.0022 pounds
600 x 0.0022 = about 1.323
Answer:
the weight in pounds is 1.324 pounds
Step-by-step explanation:
Hello, i can help you with this, you can easily solve this by using a rule of three, also you need to know
1 pound = 453 grams
Step 1
establish the relation
1 pound ⇔ 453 grams
x pound ⇔ 600 grams
the relation is
[tex]\frac{1}{453} =\frac{x}{600}\\ solve\ for\ x\\x=\frac{1*600}{453}\\x=1.324\\[/tex]
so, the weight in pounds is 1.324 pounds
I really hope It helps , have a nice day.
a first number plus twice a second number is 7 twice the first number plus the second totals 29 find the numbers
Final answer:
The student's question involving a system of equations can be solved to find that the two numbers are 17 and -5. By setting up a system of equations based on the given conditions and solving it using the elimination method, we obtain the values for the two unknown numbers.
Explanation:
System of Equations to Find Two Numbers
Let's define the first number as x and the second number as y. The problem states that x plus twice y equals 7 and twice x plus y equals 29. These statements can be turned into a system of linear equations:
x + 2y = 7
2x + y = 29
Using the substitution or elimination method, we can solve these equations for x and y. First, multiply the first equation by 2 to align the coefficients of x:
(2)(x) + (2)(2y) = (2)(7)
The equations now become:
2x + 4y = 14
2x + y = 29
Subtracting the second equation from the first gives us:
3y = -15
Divide both sides of this new equation by 3 to get the value of y:
y = -5
Now that we have a value for y, substitute it back into one of the original equations to find x:
x + 2(-5) = 7
x - 10 = 7
x = 17
The two numbers that solve the system are x = 17 and y = -5.
Find the original price if the sale price of the cell phone is $205.50
Answer:
$293.6
Step-by-step explanation:
Here is the complete question: A cell phone is on sale for 30% off. Find the original price if the sale price of the cell phone is $205.50.
Given: Sale price of cell phone is $205.50
Discount= 30%
As 30% discount is given on original price or we can say 70% of original price is $205.50.
∴ Let the original price be x.
⇒ [tex]\frac{70}{100} \times x= 205.50[/tex]
Now, cross multiplying both side.
⇒ [tex]x= \frac{100}{70} \times 205.5[/tex]
∴ x= $293.6
The original price of cell phone is $293.6.
Incline mats, or triangle mats, are offered with different levels of incline to help gymnasts learn basic moves. As the name may suggest, two sides of the mat are right triangles. If the height of the mat is 28 inches shorter than the length of the mat and the hypotenuse is 8 inches longer than the length of the mat, what is the length of the mat?
Answer:
The length of the mat is 60 in.
Step-by-step explanation:
Given :
Mats are inclined to form a triangle.
two sides of the mat are right triangles.
Hence the triangle formed is right angled triangle.
Let the length be x.
Now,The height of the mat is 28 inches shorter than the length of the mat.
Height of mat = x - 28
Also, the hypotenuse is 8 inches longer than the length of the mat.
Hypotenuse = x + 8
Hence by using Pythagoras theorem we get ,
[tex]Hypotenuse^2= lenght^2+height^2\\[/tex]
[tex]x^2+(x-28)^2=(x+8)^2\\x^2+x^2-56x+784=x^2+16x+64\\x^2-72x+720=0\\x^2-60x-12x+720 = 0\\x(x-60)-12(x-60)=0\\(x-12)(x-60) = 0\\x-12=0\\x=12\\x-60=0\\x=60[/tex]
Now we get 2 values of length 12 and 60.
But height is 28 in less than length.
And when we take length value as 12 the height will be negative hence it can't be true.
Hence the Length of mat = 60 in.
Solve for x 4x+8=7.8+5x
4x+8=7.8+5x
Subtract 4x from both sides:
8 = 7.8 +x
Subtract 7.8 from both sides:
x = 0.2
Chris's new car gets 42 miles per gallon. What is the equation that represents y, the total miles driven on x gallons of gas? x = 42 + y y = 42 + x y = 42x x = 42y
Answer:
y = 42x
Step-by-step explanation:
Answer:
The answer is y=42x
44. What percent of 75 is 30?
Answer:
40%
Step-by-step explanation:
30/75 = 0.4
Move decimal point back 2 places to convert to percent.
0.4 = 40%
Answer: 40%
Step-by-step explanation:
let x equal the percent
75x=30
x=2/5=40%
The manager of a movie theater found that Saturdays sales were $3675. He knew that a total of 650 tickets were sold on saturday. Adult tickets cost $7.50, and children tickets cost $4.50. How many of each kind of ticket were sold?
Answer:
Adults= 250 tickets
Children= 400 tickets
Step-by-step explanation:
Answer
250 adult tickets were sold and 400 children tickets were sold
Step by Step Explanation:
Given
Saturday Sales: $3675
Total tickets: 650
Cost of adult tickets = $7.50
Cost of children tickets = $4.50
Let A represent the adult tickets and C represent the children tickets,
if there's a total of 650 tickets, then
A + C = 650
Also,
if an adult ticket cost $7.50 and a child ticket cost $4.50 then
7.5A + 4.5C = 3675
From these, we have a simultaneous equation
A + C = 650 ------- (1)
7.5A + 4.5C = 3675 ----------(2)
Make A the subject of formula in (1)
A + C = 650 becomes
A = 650 - C
Substitute 650 - C for A in (2), we have
7.5(650 - C) + 4.5C = 3675
Open the bracket
4875 - 7.5C + 4.5C = 3675
4875 - 3C = 3675
Collect like terms
-3C = 3675 - 4875
-3C = -1200
Divide through by -3
[tex]\frac{-3C}{-3} = \frac{-1200}{-3}[/tex]
C = 400
Recall that
A = 650 - C
So, A = 650 - 400
A = 250
Hence, 250 adult tickets were sold and 400 children tickets were sold
Delila has 4 coins. If Delila flips all the coins at once, how many outcomes are in the sample space?
Answer:0
Step-by-step explanation:
because once you flip all of them there all in the air and there flipped
What is the inequality?
y=x+5 y=3x solving systems by substitution
Answer:
x=5/2, y=15/2. (5/2, 15/2).
Step-by-step explanation:
y=x+5
y=3x
---------
x+5=3x
5=3x-x
5=2x
x=5/2
y=3(5/2)=15/2
Please answer with evidence!!!!!
Without multiplying, determine the sign of the product (356,864)(−194,758). (5 points)
Group of answer choices
The sign of the product is positive because a positive multiplied by a negative is a positive.
The sign of the product is negative because a positive multiplied by a negative is a negative.
The sign of the product is negative because the second number is negative.
The sign of the product is positive because the first number is positive.
Answer:
The sign of the product is negative because a positive multiplied by a negative is a negative.
Step-by-step explanation:
Since you asked for evidence I will multiply even though the question asks you to solve without multiplying.
1×-1=-1
-1×-1=1
1×1=1
A negative multiplied by a positive is always negative. Doesn't matter which order you put it in. Meaning a positive multiplied by a negative is also always negative.
A positive multiplied by a positive is always positive.
A negative multiplied by a negative is always positive.
356,864 × −194,758 = negative sign answer
Cameron is making pumpkin bread. The recipe calls for 4 3/4 cups of flour. She has 2 2/3 cups. How much more flour does she need?
Answer:
25/12 or 2 1/12
Step-by-step explanation:
4 3/4=19/4
2 2/3=8/3
19/4-8/3=57/12-32/12=25/12
Four times a number added to 8 times the number equals 48. Find the number
Answer:
4*6+8*6=48
Step-by-step explanation:
Answer:
The number is 4.
Step-by-step explanation:
4x+8x=48
12x=48
x=48/12
x=4
Determine whether the ratio are equivalent
18 trucks and 4 cars
21 trucks and 6 cars
These two ratios are not equivalent, as 18 trucks and 4 cars simplifies to a ratio of 9:2, while 21 trucks and 6cars simplifoes down to a ratio of 7:2. Obviously, there is a difference between 9:2 and 7:2, so they are not equivalent.
Rewrite the expression using distributive property : 30x + 6
Answer:
This cannot be done, but it can be factored as: 6(5x + 1)
Step-by-step explanation:
This expression cannot be distributed any further.
The distributive property is used when multiplying polynomials (multiplying one or more terms by two or more terms). In which case, each term in multiplied by each of the terms in the bracket, for example: .
5(x + 2) = 5x + 10
We can factor this expression however to go the opposite direction:
30x + 6
Since 30 and 6 are both divisible by 6, we can factor it out of each term.
Divide 30x by 6 and divide 6 by 6.
6(5x + 1)
i need help plsss n ty
Answer
○ A. [tex]\displaystyle y - 5 = 2(x - 10)[/tex]
Step-by-step explanation:
First, find the rate of change [slope]:
[tex]\displaystyle \frac{-y_1 + y_2}{-x_1 + x_2} = m \\ \\ \frac{-5 - 7}{-10 + 4} = \frac{-12}{-6} = 2[/tex]
Then, according to the Point-Slope Formula, [tex]\displaystyle y - y_1 = m(x - x_1),[/tex]all the negative symbols give the OPPOSITE terms of what they really are, so be EXTREMELY CAREFUL inserting the coordinates into the formula with their CORRECT signs:
[tex]\displaystyle y - 5 = 2(x - 10)[/tex]
I am joyous to assist you anytime.
Number sentence same sum as 50+6=56
Answer:
The sum of 50 and 6 is the total of 56
Answer:
Fifty plus six equals fifty-six.
John wrote that 5 + 5 = 10. Then wrote that 5 + 5 + n = 10 + n. Are the equations John wrote equivalent? Explain.
Equation 5 + 5 = 10 and 5 + 5 + n = 10 + n are equivalent equation
Solution:Given that
John wrote that 5 + 5 = 10 ------ (1)
Then wrote that 5 + 5 + n = 10 + n ------ (2)
Need to determine are the equations written by John are equivalent.
First we need to keep in mind that whenever we apply same operation like addition, subtraction, multiplication and division on both the sides of equation that is left hand side and right hand side, we get the equivalent equation.
As in the second equation John added same value that is n on both sides of equation, we can say that equation with n is equivalent to the previous equation without n
Other way is let’s solve equation (2) and see if we can get equation (1)
5 + 5 + n = 10 + n
On subtracting both the sides with n we get,
5 + 5 + n – n = 10 + n – n
=> 5 + 5 = 10 which is same as equation (1)
Hence we can conclude that equation 5 + 5 = 10 and 5 + 5 + n = 10 + n are equivalent equation.
Final answer:
The equations 5 + 5 = 10 and 5 + 5 + n = 10 + n are equivalent because adding the same number 'n' to both sides of an equation does not change the original equality.
Explanation:
Yes, the equations that John wrote are equivalent. The first equation, 5 + 5 = 10, establishes that the sum of five plus five equals ten. The second equation, 5 + 5 + n = 10 + n, simply adds n to both sides of the first equation. This does not change the equality because, according to the properties of equality, if you add the same amount to both sides of an equal sign, the two sides remain equal. This can also be seen as an application of the commutative property of addition which states that numbers can be added in any order without changing the sum, as in A + B = B + A. Therefore, the original sum of 5 + 5 on the left side remains 10 when n is added to both sides, showing that 5 + 5 + n is indeed equal to 10 + n.
Question 15 (2.5 points)
Which ordered pair could replace the missing value and create a
function?
{(8,5), (2, 3), (1,6), (7,4), _?_}
O (3, 6)
(2,0)
(7,9)
(1,3)
(3, 6) can replace the missing value and create a function
Step-by-step explanation:
Given relation is:
{(8,5), (2, 3), (1,6), (7,4), _?_}
In order for a relation to be a function, the first condition is that there should be no repetition in domain of the function i.e. same input cannot map to multiple outputs.
In the form of ordered pairs, the first element of each ordered pair represents the elements of domain set
So,
From all the option given, only (3,6) is suitable to be put in the blank space as it will create no repetition in the domain while other ordered pairs will cause repetition.
Hence,
(3, 6) can replace the missing value and create a function
Keywords: Relations, functions
Learn more about functions at::
brainly.com/question/10940255brainly.com/question/10941043#LearnwithBrainly
Helppp me pls I can’t figure this out
Answer:
A=F
Step-by-step explanation:
It's the congruency
Find the values of x and y that make these triangles congruent by the HL Theorem.
Answer:
x = 2y
x + 4 = 3y + 1
2y + 4 = 3y + 1
y = 3, x = 6
HELP ASAP 100PTS PART A AND PART B
DONT COPY OTHERS I CAN TELL AND REPORT YOU
A scientist is studying the growth of a particular species of plant. He writes the following equation to show the height of the plant f(n), in cm, after n days:
f(n) = 10(1.02)n
Part A: When the scientist concluded his study, the height of the plant was approximately 11.04 cm. What is a reasonable domain to plot the growth function?
Part B: What is the average rate of change of the function f(n) from n = 1 to n = 5, and what does it represent?
Answer:
Part A) The reasonable domain to plot the growth function is the interval [0,5]
Part B) The average rate of change is [tex]0.21\ \frac{cm}{day}[/tex]
see the explanation
Step-by-step explanation:
Part A)
Let
f(n) -----> the height of the plant in cm
n ----> the number of days
we have
[tex]f(n)=10(1.02)^n[/tex]
This is a exponential function of the form
[tex]f(x)=a(b)^x[/tex]
where
a is the initial value
b is the base
r is the rate of growth
b=(1+r)
In this problem we have
[tex]a=10\ cm[/tex] ----> initial value or y-intercept
[tex]b=1.02\\r=b-1=1.02-1=0.02\\r=2\%[/tex]
For f(n)=11.04 cm
Find the value of n
substitute in the exponential function
[tex]11.04=10(1.02)^n\\11.04/10=(1.02)^n\\1.104=(1.02)^n[/tex]
Apply log both sides
[tex]log(1.104)=(n)log(1.02)\\n=log(1.104)/log(1.02)\\n=5\ days[/tex]
so
The reasonable domain to plot the growth function is the interval -----> [0,5]
[tex]0 \leq x \leq 5[/tex]
Part B) What is the average rate of change of the function f(n) from n = 1 to n = 5, and what does it represent?
the average rate of change is equal to
[tex]\frac{f(b)-f(a)}{b-a}[/tex]
In this problem we have
[tex]f(a)=f(1)=10(1.02)^1=10.2\ cm f(b)=f(5)=10(1.02)^5=11.04\ cm\\a=1\\b=5\\[/tex]
Substitute
[tex]\frac{11.04-10.2}{5-1}=0.21\ \frac{cm}{day}[/tex]
The average rate of change is the change of the function values (output values) divided by the change of the input values.
That represent ----> The plant grew an average of 0.21 cm per day during that time interval
"Part A) The reasonable domain to plot the growth function is the interval [0,5]
Part B) The average rate of change is
see the explanation
Step-by-step explanation:
Part A)
Let
f(n) -----> the height of the plant in cm
n ----> the number of days
we have
This is a exponential function of the form
where
a is the initial value
b is the base
r is the rate of growth
b=(1+r)
In this problem we have
----> initial value or y-intercept
For f(n)=11.04 cm
Find the value of n
substitute in the exponential function
Apply log both sides
so
The reasonable domain to plot the growth function is the interval -----> [0,5]
Part B) What is the average rate of change of the function f(n) from n = 1 to n = 5, and what does it represent?
the average rate of change is equal to
In this problem we have
Substitute
The average rate of change is the change of the function values (output values) divided by the change of the input values.
That represent ----> The plant grew an average of 0.21 cm per day during that time interval"quoted from
"calculista"
What symbol would you use to write an algebraic expression for "three divided by a number?"
A. +
B. −
C. ×
D. ÷
Answer:
D: is the answer
Step-by-step explanation:
A. + add
B. − subtract
C. × multiply
D. ÷ divide (can also be written with a "/") as in 3/2 vs 3÷ 2
The symbol used to write an algebraic expression for "three divided by a number" is the division symbol, ÷. We write this based off the description as '3 ÷ n' or '3/n' in fractional form.
Explanation:To write an algebraic expression for "three divided by a number," you would use the division symbol which is represented as ÷. So, if our unknown number is represented by the letter 'n', the algebraic expression would be written as "3 ÷ n" or "3/n" in fractional form.
In an algebraic expression, each symbol represents a specific mathematical action. The '+' symbol is for addition, '-' is for subtraction, 'x' is for multiplication, and '÷' is for division. In this case, since the problem specifies division, the correct symbol to use would be '÷'.
Learn more about Algebraic expressions here:https://brainly.com/question/34192827
#SPJ11
A number added to itself equals 5 less than the number
Answer:
The number is -5.
Step-by-step explanation:
x+x=x-5
2x=x-5
x-2x=5
-x=5
x=-5
4. A local bakery sold 60 loaves of bread in one day. If 65%
of these were sold in the afternoon, how many loaves were
sold in the afternoon?
Answer: 39 loaves were sold in the afternoon
Step-by-step explanation: So basically what you do here is divide 60 by 100. That makes 0.6, 0.6 equals 1%. (60 equals 100% and that why you divide by 100) Now, you multiply 0.6 by 65. the answer is 39. 65% of the bread is 39 loaves. So 39 loaves were sold in the afternoon.
Have an amazing day! :)
Answer:
60 x 65% = 39
So 39 were sold in the afternoon
Step-by-step explanation:
To convert the TUU UI
1
1.
What are numbers when Rs 880 is divided in to the ratio of 1 by 5 is to 1 by 6
Answer:
The ratio of 1 by 5 is to 1 by 6 is Rs 176 : Rs 146.67
Step-by-step explanation:
The given amount here = Rs 880
Now let us assume the 1 by 5 of Rs 880 = m
and assume 1 by 6 of the amount Rs 880 =n
To Find m : n
Now, [tex]\frac{1}{5} \times 880 = m\\\implies m =176[/tex]
or, 1 by 5 = 176
Similarly: [tex]\frac{1}{6} \times 880 = n\\\implies n =146.6666[/tex]
or, 1 by 6 = 146.67
⇒ m : n = 176 : 146.67
Hence, the ratio of 1 by 5 is to 1 by 6 = Rs 176 : Rs 146.67
1+9i and 5-3i midpoint
Answer:6i-6
Step-by-step explanation:
9i-3i=6i
1+5=6
Garth has a summer job and earns $9.32 per hour. One week, he works
16 3/4 hours. He deposits $150 in a bank and decides to use the rest of the money to buy raffle tickets. Each raffle ticket costs $0.50. How many raffle tickets can Garth buy?
Answer:
12.22
Step-by-step explanation:
I don't know if 12.22 is an answer for you but if it's not I would round to 12. What you do is multiply 9.32 by 16 3/4 which gives you 156.11. Take 156.11 and subtract 150 since Garth is putting that in the bank which leaves you with 6.11. Lastly you will divide 6.11 by .5 which will give you 12.22. So Garth can buy 12 raffle tickets.
Answer:
Garth can buy 12 raffle tickets.
Step-by-step explanation:
This is because when you multiply 9.32 with 16, it is 149.12.
Then, each quarter an hour, or 15 minutes, he earns 2.33 dollars.
Multiply by 3 and you get 6.99.
Add 6.99 with 149.12 and you get 156.11
Get rid of 150$ and you have 6.11
Each dollar you can get 2 raffle tickets.
So 6 dollars or 6, multiplied by 2 is 12.
Hope this helps you!
P.S If I may, can I please have brainliest, I would greatly appreciate it.
Inverse for h(x)=2x-4/3
Answer:
[tex]y=\frac{x}{2}+\frac{2}{3}[/tex]
Step-by-step explanation:
The inverse function [tex]f^{-1}[/tex] of a function [tex]f[/tex] must meet that if [tex]f(a)=b[/tex], then [tex]f^{-1}(b)=a[/tex]. To find the inverse function one can clear out x from the initial equation, and once obtained an expression x=f(y), replace x by y, where y=f(x).In this case, [tex]y=h(x)=2x-\frac{4}{3}[/tex].To find the inverse function, we clear out x, as follows: [tex]y=2x-\frac{4}{3}[/tex]⇒[tex]y+\frac{4}{3} =2x[/tex]⇒[tex]x=\frac{y}{2}+\frac{2}{3}[/tex].Now that we have clear out the value of x as a function of y, we just have to replace x by y: [tex]y=\frac{x}{2}+\frac{2}{3}[/tex], which is the inverse function we have been looking for.To corroborate the function is correct, we can use the fact that [tex]f(a)=b[/tex], then [tex]f^{-1}(b)=a[/tex]. If we take x=1, in the first equation [tex]f(1)=2-\frac{4}{3} = \frac{2}{3}[/tex]. If now we replace b=2/3 in the inverse function we obtain [tex]f^{-1}(\frac{2}{3})=\frac{\frac{2}{3} }{2} +\frac{2}{3} =1[/tex]Charlie guesses that his dog weighs 34.5 pounds. The dog actually weighs 32.7 pounds.
What is the percent error in Charlie’s guess, to the nearest tenth of a percent?
0.05%
0.5%
5.2%
5.5%
Answer:
error pecentage is 5.5% i think because 1.8 divde by 32.7 is 0.5504... * 100 is 5.504
Step-by-step explanation:
The percent error in Charlie's guess regarding his dog's weight is 5.5%, calculated using the difference between the actual and estimated values divided by the actual value, times 100%.
Explanation:To calculate the percent error in Charlie's guess, we use the formula for percent error which is:
Percent Error = (|Actual Value - Estimated Value| / Actual Value) × 100%
Substitute the values into the formula:
Percent Error = (|32.7 - 34.5| / 32.7) × 100%
Percent Error = (1.8 / 32.7) × 100%
Percent Error = 0.054983922826 × 100%
Percent Error = 5.5% (rounded to the nearest tenth)
Therefore, the percent error in Charlie's guess is 5.5%.